2011
DOI: 10.3324/haematol.2011.050203
|View full text |Cite
|
Sign up to set email alerts
|

Detection of minimal residual disease following induction immunochemotherapy predicts progression free survival in mantle cell lymphoma: final results of CALGB 59909

Abstract: ConclusionsDetection of minimal residual disease following induction immunochemotherapy was an independent predictor of time to progression following immunochemotherapy and autologous stem cell transplantation for mantle cell lymphoma. The clinical trial was registered at ClinicalTrials.gov: NCT00020943.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
60
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 26 publications
6
60
0
Order By: Relevance
“…Limited data exist regarding the use of polymerase chain reaction (PCR) amplification of immunoglobulin heavy chain rearrangements or flow-cytometry-based minimal residual disease (MRD) measures and outcome in MCL(21-23). These studies only included patients in prospective clinical trials using patient-specific PCR assays, and few data exist regarding the application of this strategy to an unselected population of MCL patients undergoing ASCT when routine clinical testing is employed.…”
Section: Introductionmentioning
confidence: 99%
“…Limited data exist regarding the use of polymerase chain reaction (PCR) amplification of immunoglobulin heavy chain rearrangements or flow-cytometry-based minimal residual disease (MRD) measures and outcome in MCL(21-23). These studies only included patients in prospective clinical trials using patient-specific PCR assays, and few data exist regarding the application of this strategy to an unselected population of MCL patients undergoing ASCT when routine clinical testing is employed.…”
Section: Introductionmentioning
confidence: 99%
“…Four studies consistently reported that the presence of or the relative content of tumor cells in the stem cell product did not affect further clinical outcome. 5,16,29,31 This could indicate that tumor cells contaminating the reinfused stem cells might not be able to cause or promote clinical progression, and that cytoreduction in the involved tissues by induction and consolidation treatment has the strongest impact on tumor control.…”
Section: Prognostic Value Of Mrd Before High-dose Consolidationmentioning
confidence: 99%
“…28 Several smaller studies have also shown the prognostic value of MRD status after various induction immunochemotherapies and before high-dose consolidation. [29][30][31][32] As far as ASCT is concerned, the question arises whether the presence of MRD in the stem cell product re-transfused is associated with inferior PFS. Four studies consistently reported that the presence of or the relative content of tumor cells in the stem cell product did not affect further clinical outcome.…”
Section: Prognostic Value Of Mrd Before High-dose Consolidationmentioning
confidence: 99%
“…Several studies have confirmed, not surprisingly, that the achievement of molecular remission (MR; i.e., molecular CR) in peripheral blood and/or bone marrow following induction immunochemotherapy is significantly associated with a better outcome, independently of other prognostic variables in both elderly and younger patients (34,63), and should become the goal in upcoming or ongoing immunochemotherapy trials (64).…”
Section: Assessment Of Quality Of Response To Predict Outcomes: Mrd Amentioning
confidence: 99%